Petway, Carlton - Nashville, TN. - Metro Councilman - Thru 1973: 1973 (1973)
Special Collections -- Banner Archives -- Clippings -- Drawer 4134

Petway, Carlton, Jr. - Nashville, TN. - Drug Charges
Special Collections -- Banner Archives -- Clippings -- Drawer 4134

Petway, Carlton - Nashville, TN. - Metro Councilman - 1974 - Attorney - Deceased Sept. 1991: 1974-1991 (1974)
Special Collections -- Banner Archives -- Clippings -- Drawer 4134